PENGARUH PENILAIAN DAN MENTORING TERHADAP PENINGKATAN KINERJA KARYAWAN RUMAH SAKIT ISLAM NASRUL UMMAH - Moch Bayu Hindarto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Employee performance is very influential on the service of a hospital. This study aims to determine the effect of performance appraisal and mentoring on employee performance at The Islamic Hospital Nasrul Ummah of Lamongan. The population of this study were all hospital employees from health workers, pharmacists and other administrative divisions. This study used a sample of 76 (seventy-six) people with a random sampling method. Data analysis used multiple linear regression with SPSS Statistics 26 for Mac from IBM. The effect of performance appraisal and mentoring is positively significant. Nasrul Ummah Islamic Hospital must continue to performance appraisal and mentoring its employees to maintain their performance well to attract people to choose Nasrul Ummah Islamic Hospital over another hospital.